Functional characterization of detergent-decellularized equine tendon extracellular matrix for tissue engineering applications. - Daniel W Youngstrom (Public Library of Science (PLoS), 2013)
Natural extracellular matrix provides a number of distinct advantages for engineering replacement orthopedic tissue due to its intrinsic functional properties. The goal of this study was to optimize a biologically derived scaffold for tendon tissue engineering using equine flexor digitorum superficialis tendons. We investigated changes in scaffold composition and ultrastructure in response to several mechanical, detergent and enzymatic decellularization protocols using microscopic techniques and a panel of biochemical assays to evaluate total protein, collagen, glycosaminoglycan, and deoxyribonucleic acid content. Biocompatibility was also assessed with static mesenchymal stem cell (MSC) culture. Implementation of a combination of freeze/thaw cycles, incubation in 2% sodium dodecyl sulfate (SDS), trypsinization, treatment with DNase-I, and ethanol sterilization produced a non-cytotoxic biomaterial free of appreciable residual cellular debris with no significant modification of biomechanical properties. These decellularized tendon scaffolds (DTS) are suitable for complex tissue engineering applications, as they provide a clean slate for cell culture while maintaining native three-dimensional architecture.